2020
DOI: 10.1002/ange.202001231
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Charging of a Perylene Bisimide Dye by Multistep Low‐Energy Solar‐Light‐Induced Electron Transfer Towards H2 Evolution

Abstract: A photocatalytic system containing a perylene bisimide (PBI) dye as a photosensitizer anchored to titanium dioxide (TiO2) nanoparticles through carboxyl groups was constructed. Under solar‐light irradiation in the presence of sacrificial triethanolamine (TEOA) in neutral and basic conditions (pH 8.5), a reaction cascade is initiated in which the PBI molecule first absorbs green light, giving the formation of a stable radical anion (PBI.−), which in a second step absorbs near‐infrared light, forming a stable PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The PTCDA anions exhibited a different color from their own that enabled them to be tested by ultraviolet-visible (UV-Vis) light irradiation 38,39 . New absorption bands of PTCDA anion appeared at ~ 668, ~755 and ~ 788 nm under irradiation of λ 350 nm, and the maximum amount of PTCDA anions was obtained when irradiated with simulated sunlight (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PTCDA anions exhibited a different color from their own that enabled them to be tested by ultraviolet-visible (UV-Vis) light irradiation 38,39 . New absorption bands of PTCDA anion appeared at ~ 668, ~755 and ~ 788 nm under irradiation of λ 350 nm, and the maximum amount of PTCDA anions was obtained when irradiated with simulated sunlight (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, inspired by the work of König and co‐workers, Würthner, Xie and co‐workers have demonstrated how carboxyphenyl‐substituted PDI s ( cp‐PDI s) can be charged consecutively with triethanolamine (TEOA) in a conPET‐type manner to cp‐PDI 2 − which when loaded onto Pt‐doped TiO 2 culminates in a highly photoactive hydrogen evolution reaction material [83f] . In their study (not shown), π‐stacking aggregation of neutral cp‐PDI was observed, and it was proposed that the further reductive PET from TEOA to cp‐PDI ⋅ − must occur by a preassembly given the ultrashort lifetime of * cp‐PDI ⋅ − (145 ps, measured by transient absorption spectroscopy) prohibiting diffusion‐controlled reductive quenching.…”
Section: Core Structures Modifications and Their Effects On Photochem...mentioning
confidence: 99%
“…Xie, Würthner and co-workers presented a consecutive charging mechanism within a single photocatalytic system for the first time for H 2 evolution that enables absorption in a wide range and covers the entire visible region of solar spectrum. [56] Perylene diimide substituted with four carboxyphenoxy groups (cp-PDI) 6 at bay position (Figure 3c) was synthesized to anchor onto TiO 2 nanoparticles loaded with Platinum. The H 2 evolution experiments were carried out in the presence of TEOA at neutral and basic (8.5) pH conditions.…”
Section: Perylene Derivatives With Tiomentioning
confidence: 99%